Corticosteroids in Duchenne muscular dystrophy: Major variations in practice. Issue 1 (25th April 2013) - Griggs, Robert C.; Herr, Barbara E.; Reha, Allen; Elfring, Gary; Atkinson, Leone; Cwik, Valerie; Mccoll, Elaine; Tawil, Rabi; Pandya, Shree; McDermott, Michael P.; Bushby, Kate
ABSTRACT Introduction: In 2004, a Cochrane Review and AAN practice parameter concluded that prednisone 0.75 mg/kg/day is of short‐term efficacy in Duchenne muscular dystrophy (DMD). Subsequent efforts to standardize care for DMD indicated wide variation in corticosteroid use. Methods: We surveyed physicians who follow patients with DMD, including: (1) clinics in the TREAT‐NMD (Translational Research in Europe—Assessment and Treatment of Neuromuscular Diseases) network (predominantly Europe) and (2) U.S. MDA clinic directors. We also documented the co‐administered corticosteroids in a trial of a putative treatment (ataluren) for DMD. Results: Of 105 Treat‐NMD clinicians, corticosteroids were not used in 10 clinics, and 29 different regimens were used—the most frequent 0.75 mg/kg/day prednisone (61 centers); 10 days on/10 days off (36 centers); 0.9 mg/kg/day deflazacort (32 centers); and 5 mg/kg/day on weekends (10 centers). Similar diversity was identified in MDA clinics and in the ataluren trial. Conclusions: Variability in corticosteroid use suggests uncertainty about risks/benefits of corticosteroid regimens for DMD. Muscle Nerve, 2013